The effect of mechanical strains in soft tissues of the shoulder during load carriage. Issue 15 (26th November 2015) - Hadid, Amir; Belzer, Noa; Shabshin, Nogah; Zeilig, Gabi; Gefen, Amit; Epstein, Yoram
Abstract: Soldiers and recreational backpackers are often required to carry heavy loads during military operations or hiking. Shoulder strain appears to be one of the limiting factors of load carriage due to skin and underlying soft tissue deformations, trapped nerves, or obstruction of blood vessels. The present study was aimed to determine relationships between backpack weights and the state of loads in the shoulder׳s inner tissues, with a special focus on the deformations in the brachial plexus. Open-MRI scans were used for developing and then verifying a three-dimensional, non-linear, large deformation, finite element model of the shoulder. Loads were applied at the strap-shoulder contact surfaces of the model by pulling the strap towards the shoulder until the desired load was reached. Increasing the strap tensile forces up to a load that represents 35 kg backpack resulted in gradual increase in strains within the underlying soft tissues: the maximal tensile strain in the brachial plexus for a 25 kg backpack was 12%, and while carrying 35 kg, the maximal tensile strain increased to 16%. The lateral aspect of the brachial plexus was found to be more vulnerable to deformation-inflicted effects than the medial aspect. This is due to the anatomy of the clavicle that poorly shields the plexus from compressive loads applied during load carriage, while the neural tissue in the medial aspect of the shoulder is better protected by the clavicle. The newly developed model can serve as a tool to estimate soft tissue deformations in the brachial plexus for heavy backpack loads, up to 35 kg. This method will allow further development of new strap structures and materials for alleviating the strains applied on the shoulder soft tissues.